Transcranial Magnetic Stimulation on spasticity in Multiple Sclerosis – protocol for a feasibility study for a randomized, crossover clinical trial - Fernanda Ishida Corrêa; Amanda Cristina da Silva Reis; Bruno Paulino Venâncio; João Carlos Ferrari Corrêa (Fisioterapia e Pesquisa)
ABSTRACT Spasticity is a common sequela of multiple sclerosis (MS) that can cause pain, deformities, and impair movement. Transcranial magnetic stimulation (TMS) has been investigated for the treatment of spasticity; however, further investigation is needed. This study aimed to compare the effect of high and low frequency TMS on quadriceps spasticity in MS. Adults diagnosed with MS and who present bilateral quadriceps spasticity will undergo two treatment sessions with TMS. The first session will be randomized to receive high (≥5Hz) or low frequency (≤1Hz) TMS over the left motor cortex; after one week they will receive the second session, which will be the opposite. Spasticity will be assessed bilaterally, before and after each intervention, using the Ashworth scale, the latency of TMS to the quadriceps muscles, the amplitude of the motor evoked potential, the central motor conduction time, the latency time of the patellar reflex, and the amplitude of the quadriceps pendulum test. Statistical analyses will be carried out using the SPSS Statistic program, version 26, with a significance level of p<0.05. The Shapiro-Wilk test will be used to analyze the normality of the variables. Parametric data will be represented as mean and standard deviation and non-parametric data will be represented as median and interquartile range, and frequency and percentage for categorical variables. For the primary outcome, the two-way analysis of variance will be used for parametric data, and the Friedman’s test for non-parametric data.